2015
DOI: 10.1007/s00277-015-2440-x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors, and outcomes of primary poor graft function after unmanipulated haploidentical stem cell transplantation

Abstract: Primary poor graft function (PGF) is a severe complication after allogeneic stem cell transplantation (SCT). The incidence, risk factors, and outcomes of PGF have not been well described, especially in the haploidentical SCT setting. We retrospectively reviewed patients who received haploidentical SCT at Peking University Institute of Hematology between January 1, 2011, and December 31, 2012. PGF was defined as persistent neutropenia (≤0.5 × 10(9) L(-1)), thrombocytopenia (platelets ≤20 × 10(9) L(-1)), and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 18 publications
3
63
3
6
Order By: Relevance
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…PPGF was associated with shorter survival time, which is consistent with the previous studies [4,8,11,12]. Numerous studies have reported risk factors that influence platelet engraftment, such as myelotoxic agent, conditioning regimen intensity, stem cell source, and number of infused CD34 + cells or MNC [5,6,11,28].…”
Section: Discussionsupporting
confidence: 87%
“…Rapid and persistent recovery of platelet count after allo-HSCT reflects good platelet graft function (GPGF), but in many cases, platelet graft function is poor. Poor platelet graft function (PPGF) may be primary (failure to achieve initial reconstitution of the peripheral platelet count) or secondary (the count initially recovers, but later declines) [4]. Previous studies have suggested several factors that are associated with the development of PPGF after allo-HSCT, including donor match of the HLA or ABO (blood group system), intensity of the conditioning regimen, and stem cell source [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Especially with the increasing use of HLA-mismatched/haploidentical allo-HSCT (HBMT) in the past 10 years, PGF has become a growing obstacle contributing to high morbidity and mortality after transplantation. [6][7] Sun et al 4 recently reported that subjects with early PGF, with an incidence of~5.6% in HBMT, have significantly poorer overall survival at 2 years than subjects with good graft function (GGF; 34.6 vs 82.7%, Po 0.001). Moreover, Chang et al 5 have identified early PGF as an independent factor for inferior survival after unmanipulated HBMT in multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Poor graft function (PGF) remains a serious complication, which affects 5% to 27% of patients and contributes to a considerably high transplant-related mortality, especially in the cases of unsatisfactory therapeutic outcomes for haploidentical donor HSCT. 2,3 Despite significant improvements made in the prevention and treatment of complications postallo-HSCT, PGF still occurs frequently due to many pre-and post-transplantation factors, such as immunologically mediated graft rejection, 4 myelotoxic agents, 5 acute and chronic graft-vs-host disease, 6 T-cell depletion, 7 viral infections, 8 conditioning regimen intensity, and stem cell sourcing. 9,10 In addition to these risk factors, impaired bone marrow (BM) microenvironment prior to allo-HSCT may also delay the hematopoietic reconstitution of successfully engrafted donor hematopoietic stem cells (HSCs), resulting in the occurrence of PGF post-allo-HSCT.…”
mentioning
confidence: 99%